2004
DOI: 10.1038/sj.ijo.0802749
|View full text |Cite
|
Sign up to set email alerts
|

At last, a weight neutral insulin?

Abstract: In the treatment of diabetes, the positive correlation between weight gain and glycaemic control is well known. Inappropriate weight gain has been demonstrated in landmark diabetes studies, with insulin or oral antidiabetic drugs. Weight increase is associated with accelerated deterioration in beta-cell function in type II diabetes, and increases in hypertension and lipid levels in both type I and type II diabetes. Concerns about increasing weight may be a barrier to initiation or to intensification of insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 34 publications
0
31
0
3
Order By: Relevance
“…Indeed, it has already been shown that after intranasal administration the rapid-acting insulin analogue aspart exerts a stronger effect on improvement of memory performance than regular human insulin [26]. Also, clinical studies indicate that insulin detemir in comparison with other long-acting insulins attenuates weight gain in type 2 diabetic patients, as summarised [47]. Because of its acylation with a fatty acid, detemir is assumed to have facilitated access to the brain due to enhanced BBB transport.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Indeed, it has already been shown that after intranasal administration the rapid-acting insulin analogue aspart exerts a stronger effect on improvement of memory performance than regular human insulin [26]. Also, clinical studies indicate that insulin detemir in comparison with other long-acting insulins attenuates weight gain in type 2 diabetic patients, as summarised [47]. Because of its acylation with a fatty acid, detemir is assumed to have facilitated access to the brain due to enhanced BBB transport.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Over the past years data have accumulated supporting the fact that insulin therapy using insulin detemir leads to both improved glycaemic control and weight stability [14], opening new perspectives for insulin therapy. However, the mechanism(s) underlying the altered weight gain with insulin detemir are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in contrast to NPH insulin, which was associated with weight gain of 0.7 to 0.8 kg over 6 months [41][42][43][44][45] 48 There was also a risk reduction for nocturnal hypoglycemia of some 50% with insulin detemir in this study. It is possible that the reduced risk of weight gain with insulin detemir might relate to the risk reduction for hypoglycemia, but other mechanisms, including a reduced ratio of peripheral:hepatic action 49 and a central effect on appetite, 50 have been suggested.…”
Section: Insulin Detemirmentioning
confidence: 99%